The effect of capital structure on profitability: an extended analysis of biotechnology companies listed on the bursa Malaysia - Sipon, Zuraidah; Mohamed Yousop, Nur Liyana (2011)
The purpose of this study is to investigate the relationship between capital structure and profitability of biotechnology companies listed on the Bursa Malaysia during a six-year period of January 2005 until December 2010. Regression analysis had been used in the estimation of functions relating the return on equity (ROE), return on asset (ROA) and gross profit margin (GM) with measures of capital structure. The results lead the study to conclude that capital structure choice, in general terms, has weak-to-no influence on the financial performance of listed biotechnology firms in Malaysia. This suggests that biotechnology companies in Malaysia prefer to use surpluses generated from profits to finance investments. It may also indicate that firms generally prefer internal funds over external funds, irrespective of the characteristics of the asset to be financed (i.e. whether it is a tangible or intangible asset).